2021
DOI: 10.18203/2394-6040.ijcmph20214598
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study for production of germ tube in Candida albicans of various pulmonary samples, by different methods in a tertiary care hospital of south west Rajasthan

Abstract: Background: Systemic candidiasis is associated with a high crude mortality rate, even with first line antifungal therapy. C. albicans is the predominant cause of invasive fungal diseases which is a serious public health issue. The main objective was to assess the reliability of different media for germ tube production in Candida albicans isolated from various clinically diagnosed pulmonary samples.Methods: All Candida isolates were identified and speciated by conventional methods such as Gram’s staining, germ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Our study highlights that around 92.79% of positivity were seen with YEPD ( Yeast Extract Peptone Dextrose) which correlates with a study conducted by KIM et al, 18 where demonstration of Germ tubes were seen within 30 minutes in YEPD at 39 0 C but after 60 min in serum at 37 0 C. Whereas study conducted by Bhumla et al, 19 showed 81.25% production of germ tube production with YEPD and another study carried out by Abiroo Jan et al, 20 showed 89.30% germ tube production but only in Candida albicans and no germ tube formation in candida dubliniensis.…”
Section: Discussionsupporting
confidence: 89%
“…Our study highlights that around 92.79% of positivity were seen with YEPD ( Yeast Extract Peptone Dextrose) which correlates with a study conducted by KIM et al, 18 where demonstration of Germ tubes were seen within 30 minutes in YEPD at 39 0 C but after 60 min in serum at 37 0 C. Whereas study conducted by Bhumla et al, 19 showed 81.25% production of germ tube production with YEPD and another study carried out by Abiroo Jan et al, 20 showed 89.30% germ tube production but only in Candida albicans and no germ tube formation in candida dubliniensis.…”
Section: Discussionsupporting
confidence: 89%
“…Unlike plasma, such as CPDA, Citrate or EDTA plasma in this study which can be found easier in laboratories or blood bank units. Researches on several commercial media that is particularly available in the laboratory also showed that the average times of germ tube formation on those media were longer compared to serum [21,22]. Another research succeeded in proving that the germ tube test had the same effectiveness as phenotypic methods, such as PCR.…”
Section: Discussionmentioning
confidence: 99%